ANALISIS PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (Studi pada PT Kereta Api Indonesia (Persero) DAOP IV Semarang) - Siwi, Iga Swandaru; Rahardjo, Mudji (Faculty of Economics and Business Diponegoro University, 2015)
Management of railway transportation not only focuses on services and income earned, but also the proper management of human resources. Human resources is an important factor in the success of a company achieve its goals. The success of a company is of course determined by the performance of its employees. Employee performance is strongly influenced by the role of the leader of the transformational leadership style within the company that can inspire employees and who can match its objectives with employee values. Compatibility of individual behavior with organizational culture that is applied to determine the individual's career in the future. The research is also based on the research gap found in previous research between Raed Awamleh (2005), Sapna Rijal (2010) and Ni Made Ria Satyawati & I Wayan Suartana (2014). The purpose of this research is to explain the effect of transformational leadership style and organizational culture on employee performance.The data in this study were collected through a questionnaire distributed to 70 employees in PT Kereta Api Indonesia (Persero) DAOP IV Semarang. Mechanical testing of the data used in this study include testing instrument, the classical assumption test, multiple linear regression analysis, test T-test, test F and test the coefficient of determination (R2) with the application of SPSS 17.0.The results showed that transformational leadership style and organizational culture has a positive and significant impact on employee performance. This shows the variables of transformational leadership style and organizational culture capable of improving the performance of employees at PT Kereta Api Indonesia (Persero) DAOP IV Semarang.